ANALISIS KINERJA KEUANGAN DENGAN METODE RADAR PADA PT SEMEN BATURAJA (PERSERO) TBK - Mardiana, Siska; Muhammad Danial, R. Deni; Sunarya, Erry (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2019)
The purpose of this study is to assess the financial performance of PT Semen Baturaja (Persero) Tbk by comparing the performance of PT Semen Baturaja (Persero) Tbk in several similar companies that have been listed on the Indonesia Stock Exchange. The data used are financial statement data of PT Indocement Tunggal Prakarsa Tbk, PT Semen Baturaja Persero Tbk and PT Holcim Indonesia Tbk for the period 2015-2017. The research method used is descriptive with quantitative data. The analysis technique used with the radar method. Radar analysis includes 5 ratios, namely profitability, productivity, asset utility, stability and growth potential. The results showed that the best profitability ratio of PT Semen Baturaja (Persero) Tbk,  from the best productivity ratio of PT Holcim Indonesia Tbk, was seen from the best utility ratio of PT Indocement Tunggal Prakarsa Tbk, on the stability ratio of PT Holcim Indonesia Tbk and on the best growth potential of PT Semen Baturaja (Persero) Tbk.